Comparison of conventional panoramic radiography and panoramic digital subtraction radiography in detection of simulated lesions of mandibular condyle - Panjnoush M.; Ghoncheh Z.; Sarrafzadeh A. (Tehran University of Medical Sciences, 2008)
"n  "nBackground and Aim: Digital subtraction Radiography (DSR) is a method of accurate assessing condylar head changes. several studies have been carried out in applying DSR in dentistry, however there is a few number of studies in efficacy of DSR method in assesment of condylar head changes, The aim of this study was to compare panoramic radiography and DSR detecting simulated lesions of the mandibular condyl. "nMaterials and Methods: this was a process reaserch study, in which two dry human skulls with no obvious temporomandibular joint pathology were used. Osteophytic lesions were simulated using three sizes of bone chips that were placed on the medial portion of anterior and superolateral aspects of the condyle. Osteolytic lesions were simulated making 1 and 2 mm holes using round burr in the central portion of anterior aspect and Lateral pole of the condyle. Panoramic radiographs were prepared with and without the lesions in place. These paired radiographs were digitized and digital- subtraction images of the original panoramic images were obtained. Eight observers evaluated 155 images of each modality for the presence or absence and the type of simulated lesions of the mandibular condyle. Sensitivity, specificity, reliability and measure of agreement were analyzed using kappa test and crossed tables and qualitative variables were assess by chi-square and fisher's Exact test. "nResults: Specificity of panoramic and DSR methods were 15.4% and 66.7% respectively. Sensitivity of panoramic and DSR methods were 61.1% and 80.6% for osteophytic lesions and 37.5% and 83.3% for Osteolytic lesions. The percentage of correct decisions made in DSR method was significantly more than conventional panoramic method (82.6% vs 41.9%) (p<0.0001). "nConclusion: Based on the results of this study digital subtraction technique was significantly more accurate than the panoramic radiographs in detection of simulated lesions of the mandibular condyle.